Providing Physiotherapy Education for Tension Type Headache At Sanan Tempe Chips Workers, Malang City: Pemberian Edukasi Fisioterapi Untuk Tension Type Headache Pada Pekerja Keripik Tempe Sanan Kota Malang - Anni Afifatus Shalihah; Anita Faradilla Rahim; Dony Oktavianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Tension Type Headache (TTH) or tension type headache is the most common type of headache, especially in workers. The prevalence of TTH in workers is 28.3%, so it is important to know. This educational activity took the target group of Sanan tempeh chips workers. The aim of the activity is for workers in the target group to understand tension type headaches, including signs, symptoms, prevention and treatment. The method used is physiotherapy education and exercise. Posters are used as an educational medium for health promotion. The results of the education implementation can increase the knowledge of Sanan tempe chips workers in Malang City regarding tension type headaches, and understanding of training techniques to overcome them.